A rating system for the real estate market - Renigier-Biłozor, Małgorzata; Chmielewska, Aneta (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
The authors propose rating as a new instrument providing objective comparability criteria to classify the residential market. Nowadays we face the growing popularity of various support systems, but comprehensive and effective information systems that facilitate the real estate market continue to be in short supply. The rating methodologies from the capital markets cannot be simply copied to the real estate market. The specificity of the real estate market is totally different. The main aim of this study was the development of a rating procedure for residential markets as a specific instrument to help in the making of reliable decisions within urban development. The classification was conducted on the basis of factors that can have the most important influence on property market decision-making for demand and supply relating to residential, economic and political, social, spatial and location market conditions. The crucial stage in this methodology was the establishing of the benchmark point (BB) distinguished by stimulants or destimulants of the markets. This point might represent the level of similarities (or indiscernibilities, as in rough set theory) of the features in the set. The results demonstrate that the rating of residential markets depends on the expectation of further area development and quality of life rather than the richness of a region
Argumenta Oeconomica, 2019, Nr 2 (43), s. 427-458
Keywords: rating; real estate market; competitive markets; decision support system